Subaltern counter-urbanism: Work, dispossession and emplacement in Gurgaon, India. Issue 92 (June 2018) - Cowan, Thomas
Abstract: This paper draws on field research carried out on two struggles at auto parts factories in Gurgaon between 2014 and 2015. Drawing on workers' accounts from the two struggles, I am concerned with how we might think about the women workers struggle, following Roy (2017) as enacting a gendered politics of emplacement. In doing so, I conceptualise the struggles as instances of subaltern counter-urbanism. Borrowing from Roy's (2011) "subaltern urbanism" and Fraser's (1990) "subaltern counter-publics" the struggles are counter-urban as they emerge from and are mobilised against conditions of urban everyday life which render women fixed into labour systems defined through hypermobility and flexibility. The struggles are equally counter-Urban as they break from hegemonic understandings of urban politics within disciplinary Urban Studies which tie subaltern political subjectivities to the itineries of territory, dis/possession and collective consumption (Roy, 2011). It will be shown that the women's struggles evoke demands for emplacement in the city that are future-oriented, speculative and always tentatively under erasure.